Too close friends - Roddie, Shen; Lambert, Sally Anne (New York : Dial Books for Young Readers, 1998)
Hippo and his neighbor Pig are very good friends until Hippo trims the hedge between their two houses.
Primary
Keywords: Friendship -- Fiction; Neighbors -- Fiction; Privacy, Right of -- Fiction; Pigs -- Fiction; Hippopotamus -- Fiction